2021
DOI: 10.1016/j.jagp.2020.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Social Connectedness for Underserved Older Adults Living With Depression: A Pre-Post Evaluation of PEARLS

Abstract: HIGHLIGHTS What is the primary question addressed by this study? Can PEARLS, a brief, home-based intervention focused on problem solving treatment and behavioral activation for low-income older adults living with depression, improve social connectedness for underserved older populations? What is the main finding of this study? PEARLS participants significantly improved on all three social connectedness constructs (social interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 42 publications
2
21
1
1
Order By: Relevance
“…Interestingly, caregivers providing care to someone in active treatment were more likely to report higher social connectedness, compared to those whose care recipient was not receiving treatment. This finding is consistent with a recent study of older adults with depression, that reported increased social connectedness in respondents who were caregivers compared to those who were not [ 41 ]. There is the possibility that caregivers in the current study perceived increased closeness with their care recipient, and/or increased their interaction with supportive health providers and community when their care recipient was in active treatment, which increased their perception of connectedness with others.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, caregivers providing care to someone in active treatment were more likely to report higher social connectedness, compared to those whose care recipient was not receiving treatment. This finding is consistent with a recent study of older adults with depression, that reported increased social connectedness in respondents who were caregivers compared to those who were not [ 41 ]. There is the possibility that caregivers in the current study perceived increased closeness with their care recipient, and/or increased their interaction with supportive health providers and community when their care recipient was in active treatment, which increased their perception of connectedness with others.…”
Section: Discussionsupporting
confidence: 92%
“…COVID-19 can bring such preexisting injuries into sharper focus and/or directly invoke their isolating effects ( Ogrodniczuk, Rice, et al, 2021 ). Our finding contrasts with recent reports that in mixed-sex and older samples, living alone moderates the association between low social connectedness and high psychological distress ( Gyasi et al, 2019 ; Steinman et al, 2021 ). Although demographic differences likely explain this difference, the current findings suggest men’s external work and recreational activities (i.e., outside of the domestic sphere) constitute primary social connectors and the COVID-19 restrictions imposed (along with desires to protect others) have significant impacts on men’s psychological distress regardless of the presence of others in their home environment.…”
Section: Discussioncontrasting
confidence: 99%
“…Findings also indicate that interviewees lived with families and could maintain social connectedness during the pandemic. Older adults can and do avoid isolation and loneliness and reduce health anxiety during the pandemic through receiving necessary emotional, financial, or other support from important social connections with families, friends, and neighbors ( 28 , 64 , 65 ). Moreover, these findings are consistent with existing ones that demonstrate that, with the assistance of ICTs, older adults can get timely health information and other health-promoting resources from robust connections ( 16 , 54 ).…”
Section: Discussionmentioning
confidence: 99%